(untitled) (Medical Forum Monthly, 2024)
Objective: The purpose of present study was to find out the relationship between helicobacter pylori infection and acute myocardial infarction Study Design: Experimental / Case control study Place and Duration of Study: This study was carried out the Biochemistry Department, Dow University of Health Sciences, Karachi from 11.02.2013 to 15.12.2013. Materials and Methods: Serum samples of age and gender matched 80 each of Cardiac and non-cardiac patients with H. Pylori were investigated for the levels of IgG and IgA by kit methods. RESULTS: Patients who were H.pyloric AMI compared to non-h.pyloric nomal had relationship with increased IgG in Acute myocardial infarction patient with H.pyloric infection as compare to control. Conclusion: The results of present study suggest that H. pylori is a new risk factor for the development of atherosclerosis and enhance the risk factor. Therefore proper treatment and diagnosis can be helpful for cardiac patients.